Numerical study of the effect of flow on bottom outlet of dam - Azman A.; Abas A.; Zawawi M.H.; Rozainy M.R.M.A.Z.; Abustan I. (American Institute of Physics Inc., 2023)
In this work, bottom outlet which is a part of dam that functional to flow a water. The design of bottom outlet is constructed by Computer-aided design (CAD) modelling and simulated using Computational fluid dynamic (CFD) software. The effect of water flow pattern, velocity and vorticity of the bottom outlet has been analyzed in this research work. Based on the result, the peak velocity occurs at the middle area of bottom outlet with amount of 146.8430 m/s and vorticity occurs at the end of bottom outlet with velocity of 16.3159 m/s. 2019 Author(s).